2021
DOI: 10.3389/fgene.2021.690264
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome and Weighted Gene Co-expression Network Analysis Identify Key Transcription Factors of Rosa chinensis ‘Old Blush’ After Exposure to a Gradual Drought Stress Followed by Recovery

Abstract: Rose is one of the most fundamental ornamental crops, but its yield and quality are highly limited by drought. The key transcription factors (TFs) and co-expression networks during rose’s response to drought stress and recovery after drought stress are still limited. In this study, the transcriptomes of leaves of 2-year-old cutting seedlings of Rosa chinensis ‘Old Blush’ from three continuous droughted stages (30, 60, 90 days after full watering) and rewatering were analyzed using RNA sequencing. Weighted gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 125 publications
0
6
0
Order By: Relevance
“…Rosa chinensis 'Old Blush' is an ancient Chinese species involved in modern rose breeding, and can be used as a model plant for studying the response of roses to drought stress. In our previous study, RcNAC72 was found to be a key transcription factor gene in response to drought stress in roses [36]. We conducted further studies on RcNAC72 in this report.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Rosa chinensis 'Old Blush' is an ancient Chinese species involved in modern rose breeding, and can be used as a model plant for studying the response of roses to drought stress. In our previous study, RcNAC72 was found to be a key transcription factor gene in response to drought stress in roses [36]. We conducted further studies on RcNAC72 in this report.…”
Section: Introductionmentioning
confidence: 72%
“…The preparation method of R. chinenesis 'Old Blush' materials used in this study was described in our previous study [36]. Normally growing rose leaves, petals, roots and stems were removed and quickly putted into liquid nitrogen and stored at −80 • C for tissue specific analysis of RcNAC72.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has found that WGCNA is more sensitive to noise in datasets and outperforms other clustering methods in detecting non-overlapping clusters or modules [39]. The WGCNA has been reported in several publications related to crop improvement [40][41][42][43][44].…”
Section: Command-line Tools 221 Weighted Correlation Network Analysis...mentioning
confidence: 98%
“…Among diverse abiotic stresses, numerous studies have shown that drought is the most adverse one, and it causes significant decreases in crop yields and quality traits ( Wang et al., 2011 ; Wang et al., 2019 ). To mitigate the harmful effects of drought, plants have evolved various physiological and molecular mechanisms, such as induction of diverse family genes and antioxidant defense systems, reinforcement or maintenance of biological membranes’ structure and properties, and accumulation of osmoprotectants (sugar, proteins, proline, and glutathione, GSH) in cells ( Chaves et al., 2003 ; El-Sharkawy, 2004 ; Najla et al., 2016 ; Sharma et al., 2017 ; Mahmood et al., 2020 ; Jia et al., 2021 ). Under drought stress conditions, the expression patterns of numerous genes are altered or induced to activate physiological and defense systems ( Savoi et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%